PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP MINAT BELI KONSUMEN PRODUK SMARTPHONE SAMSUNG TOKO FONEL PONDOK GEDE, KOTA BEKASI - Kurniawati; Hotman Napitupulu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
Purpose to analyze the effect of product quality and service quality on customer buying interest in Samsung Smart Phone products at the Pondok Gede Fonel Store. The research method uses descriptive qualitative and quantitative analysis, the analytical model used is linear regression, simultaneous and partially. The research population is the customers of the Pondok Gede Fonel Store. 60 people who bought Samsung Smart Phone products from January to April 2022 were taken as samples. The result simultaneous, product quality and service quality have a positive and significant effect on customer buying interest in Samsung Smart Phone products at the Pondeok Gede Fonel Store. Partially product quality has a significant effect on customer buying interest, and partially service quality has a significant effect on customer buying interest.